Kualitas Layanan Administrasi Akademik di Politeknik Negeri Pontianak - Along, Antonius (Jurnal Ilmiah Administrasi Publik, 2020)
This research was conducted to find out, describe and explain about the quality of academic administrative services in the Pontianak State Polytechnic by using a qualitative research method with a descriptive approach. Data collection techniques, interviews, observation and documentation, interactive data analysis models of Miles, Huberman, & Saldana (2014). The results showed that the quality of academic administration services in Pontianak State Polytechnic has not been going well, improvements need to be made by academic staff in terms of service quality. a) Improving academic service infrastructure; b) Leaders of the Pontianak State Polytechnic should provide training/ workshops on services prime; c) Control employee performance through measuring student satisfaction index activities; and d) Able to be consistent in providing services in accordance with academic service hours so that the services provided can run well.Â